Gender, sexuality and the discursive representation of access and equity in health services literature: implications for LGBT communities - MacDonnell Judith A; Daley Andrea E (BMC, 2011)
Abstract Background This article considers how health services access and equity documents represent the problem of access to health services and what the effects of that representation might be for lesbian, gay, bisexual and transgender (LGBT) communities. We conducted a critical discourse analysis on selected access and equity documents using a gender-based diversity framework as determined by two objectives: 1) to identify dominant and counter discourses in health services access and equity literature; and 2) to develop understanding of how particular discourses impact the inclusion, or not, of LGBT communities in health services access and equity frameworks.The analysis was conducted in response to public health and clinical research that has documented barriers to health services access for LGBT communities including institutionalized heterosexism, biphobia, and transphobia, invisibility and lack of health provider knowledge and comfort. The analysis was also conducted as the first step of exploring LGBT access issues in home care services for LGBT populations in Ontario, Canada. Methods A critical discourse analysis of selected health services access and equity documents, using a gender-based diversity framework, was conducted to offer insight into dominant and counter discourses underlying health services access and equity initiatives. Results A continuum of five discourses that characterize the health services access and equity literature were identified including two dominant discourses: 1) multicultural discourse, and 2) diversity discourse; and three counter discourses: 3) social determinants of health (SDOH) discourse; 4) anti-oppression (AOP) discourse; and 5) citizen/social rights discourse. Conclusions The analysis offers a continuum of dominant and counter discourses on health services access and equity as determined from a gender-based diversity perspective. The continuum of discourses offers a framework to identify and redress organizational assumptions about, and ideological commitments to, sexual and gender diversity and health services access and equity. Thus, the continuum of discourses may serve as an important element of a health care organization's access and equity framework for the evaluation of access to good quality care for diverse LGBT populations. More specfically, the analysis offers four important points of consideration in relation to the development of a health services access and equity framework.